Crypto currency: essence, content, methods of regulation - Kliunya, Uladzimir L.; Chernovalov, Aleksandr V.; Chernovalov, Pawel A. (Journal of the Belarusian State University. Economics, 2018)
The article analyses the functionality of bitcoin in terms of realizing basic functions assigned to money as an economic category. Bitcoin can be referred to as money, however, to a limited extent. It carries out an exchange and payment function in full, but it turns out deficient as a measure of value, whereas bitcoin’s crucial imperfection results from the lack of possibility to treat it as the means allowing for value collection and its storage. In a legal sense, both in Belarus and worldwide, bitcoin is not treated as money, but its main usefulness results from the possibility of making transnational money transfers and anonymous payments, with which owning and keeping bitcoins is not related at all. Bitcoin approached as money becomes an object of social demand due to its utility function connected with the entire spectrum of its economic (and social) functions as well as its properties allowing to meet the particular needs related to money.